The Sitcom - Mills, Brett (TV Genres : TVG, 2022)
GBS_insertPreviewButtonPopup('ISBN:9780748637522);Even though sitcom has been a consistent staple of broadcasting the world over, rigorous academic work on it as a genre remains limited. This book examines sitcom as an industry in terms of production, audiences and texts, drawing on a range of examples and case studies in order to examine the genre's characteristics, social position, and pleasures. In highlighting this long-lasting and popular form of television, it offers insights into genre theory and explores how the comic aim of sitcom forms a central characteristic of the genre.Brett Mills takes a global view of sitcom, examining international examples as well as those produced by the more dominant British and American broadcasting industries, in order to explore the relationships between sitcom, nation, and identity. Sitcoms considered include Extras, My Family, Curb Your Enthusiasm, One Foot in the Grave, Peep Show, Summer Heights High, Popetown, and Friends.Key FeaturesDraws on original research into the television industry, incorporating interviews with sitcom writers, directors and producersIncludes research on audience responses to sitcom, with reference to offence, pleasure, and social changeOffers detailed textual analyses of a range of programmes, drawing on Humour Theory to explore the ways in which jokes and comic moments workOutlines the future for sitcom, considering new media developments and the changing relationships between broadcasters and audiences